2014
DOI: 10.1155/2014/839890
|View full text |Cite
|
Sign up to set email alerts
|

Parent Training Interventions for Toddlers with Autism Spectrum Disorder

Abstract: Background. Now that early identification of toddlers with autism spectrum disorder (ASD) is possible, efforts are being made to develop interventions for children under three years of age. Most studies on early intervention have focused on intensive and individual interventions. However, parent training interventions that help parents interact and communicate with their toddlers with ASD might be a good alternative to promote the development of their child's sociocommunicative skills. Objective. This review a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
67
0
6

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 72 publications
(256 reference statements)
5
67
0
6
Order By: Relevance
“…Interventions that involve some form of parent training can be further characterized by considering the program’s format, intensity, location, duration, and target age (Beauodoin, Sebire, & Couture, 2014; Oono, Honey & McConachie, 2013; Schultz, Schmide & Stichter, 2011; Steiner et al, 2012). Format refers to how information is presented to the parent.…”
Section: Parent Training – Characterizing the Labelmentioning
confidence: 99%
See 2 more Smart Citations
“…Interventions that involve some form of parent training can be further characterized by considering the program’s format, intensity, location, duration, and target age (Beauodoin, Sebire, & Couture, 2014; Oono, Honey & McConachie, 2013; Schultz, Schmide & Stichter, 2011; Steiner et al, 2012). Format refers to how information is presented to the parent.…”
Section: Parent Training – Characterizing the Labelmentioning
confidence: 99%
“…We will present a purposive sampling of the literature to illustrate the range of characteristics in parent training interventions in ASD as well as a summary of available empirical support across the four main categories. For more comprehensive reviews of available PT programs see (Beaudoin, Sebire & Couture, 2014; Oono, Honey & McConachie, 2013; Schultz, Schmidt & Stichter, 2011). …”
Section: Parent Training – Characterizing the Labelmentioning
confidence: 99%
See 1 more Smart Citation
“…Beaudoin, Sébire, & Couture, 2014; Eldevik et al, 2010; Hampton & Kaiser, 2016; Lane, Lieberman-Betz, & Gast, 2016; Reichow, 2012; Virués-Ortega, 2010), although effects are greater for some children than others (Sallows & Graupner, 2005). EI is designed to capitalize on experience-dependent neuroplasticity, a fundamental property of the brain, by which neuronal connections are created and organized, and learning occurs in response to a child’s experiences with the environment (Kolb & Gibb, 2011).…”
Section: Neurodevelopmental Context Of Early Interventionmentioning
confidence: 97%
“…A systematic review of 15 studies involving 484 children (mean age: 23 months) showed that parents were able to implement newly learned strategies and were generally satisfied with such programs; however, findings pertaining to improvements in the children's communication and social skills were inconclusive. 28 A systematic review of nine studies of infants under 24 months of age with, or at risk for, ASD concluded that very early interventions are feasible and effective. 29 Parents reported infant gains in social-communication and developmental skills.A pilot study suggested that ASD can be identified and treated in the first year of life.…”
Section: Parent-implemented Trainingmentioning
confidence: 99%